2020
DOI: 10.1111/1471-0528.16170
|View full text |Cite
|
Sign up to set email alerts
|

The impact of chorionicity on pregnancy outcome and neurodevelopment at 2 years old among twins born preterm: the EPIPAGE‐2 cohort study

Abstract: Objective To compare the short-and mid-term outcomes of preterm twins by chorionicity of pregnancy. Design Prospective nationwide population-based EPIPAGE-2 cohort study. Setting 546 maternity units in France, between March and December 2011. Population A total of 1700 twin neonates born between 24 and 34 weeks of gestation. Methods The association of chorionicity with outcomes was analysed using multivariate regression models. Main outcome measures First, survival at 2-year corrected age with or without neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
1
9
1
Order By: Relevance
“…Premature neonates born from monochorionic pregnancies, even after TTTS, have similar long-term neurodevelopmental outcome, when compared with other twin pregnancies. 33 Second, we found no relationship between postoperative TAPS, TTTS recurrence and gestational age at laser therapy, which are major contributors to the occurrence of neurological lesions. 3 Our results support the idea of a direct correlation between gestational age at fetal therapy and perinatal outcome, as the association between survival outcomes and the gestational age at surgery remained significant after adjustment on potential severity factors.…”
Section: Discussioncontrasting
confidence: 54%
“…Premature neonates born from monochorionic pregnancies, even after TTTS, have similar long-term neurodevelopmental outcome, when compared with other twin pregnancies. 33 Second, we found no relationship between postoperative TAPS, TTTS recurrence and gestational age at laser therapy, which are major contributors to the occurrence of neurological lesions. 3 Our results support the idea of a direct correlation between gestational age at fetal therapy and perinatal outcome, as the association between survival outcomes and the gestational age at surgery remained significant after adjustment on potential severity factors.…”
Section: Discussioncontrasting
confidence: 54%
“…The near equal proportion of MZ and DZ twins with structural defects found in our cohort has not been reported previously but fits well with a recent comprehensive analysis of 1,493 twin placentas from British Columbia (Jahanfar & Lim, 2018 (Tosello et al, 2020). The same British Columbia study of twin placentas found a significantly higher risk of unequal placental sharing and abnormal anastomoses in males compared to females for both same sex twin pairs (enriched for MZ)…”
Section: The Placentasupporting
confidence: 92%
“…An excess of male twins was also observed with amyoplasia (Hall et al, 2014). Some studies of neurodevelopmental outcomes in twins include sex as a variable feature but do not report any differences, implying that any differences were not significant (Dostanic, Sustersic, & Paro-Panjan, 2018;Tosello et al, 2020). However, we predict that studies including larger numbers of twins with individual level data will support an increased risk in males based on analysis of twin placentas, discussed below (Jahanfar & Lim, 2018).…”
Section: Sex Ratiomentioning
confidence: 76%
See 1 more Smart Citation
“…Finally, the assimilation that our study suggests between sIUGR and IUGR is strictly limited to morbidity-mortality information in surviving newborns. In a recent study, the perinatal and two-year outcomes of twins born before 32 weeks were not significantly different between the monochorionic and bichorionic twin groups [35]. In other cohort studies, with inclusion to term, the number of sIUGRs was higher in monochorionic twins [36,37].…”
Section: Discussionmentioning
confidence: 78%